Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

mckayla_04

  • 4 years ago

Solve. x2 = 6x – 6

  • This Question is Closed
  1. Rohangrr
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    By ax² + bx + c = 0 form.. a = 1 b = -6 c = 6 Then, by quadratic form.. x = (-b ± √(b² - 4ac))/2a = (6 ± √((-6)² - 4*1*6))/2 = (6 ± √(36 - 24))/2 = (6 ± √12)/2 = (6 ± 2√3)/2 = 2(3 ± √3)/2 = 3 ± √3

  2. mckayla_04
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thank youuuu!!!!

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy